The digitalization and public crisis responses of small and medium enterprises: Implications from a COVID-19 survey - Guo, Hai; Yang, Zhuen; Huang, Ran; Guo, Anqi (Frontiers of business research in China, 2020)
The COVID-19 outbreak is a global crisis that has placed small and medium enterprises (SMEs) under huge pressure to survive, requiring them to respond effectively to the crisis. SMEs have adopted various digital technologies to cope with this crisis. Using a data set from a survey with 518 Chinese SMEs, the study examines the relationship between SMEs’ digitalization and their public crisis responses. The empirical results show that digitalization has enabled SMEs to respond effectively to the public crisis by making use of their dynamic capabilities. In addition, digitalization can help improve SMEs’ performance. We propose a theoretical framework of digitalization and crisis responses for SMEs and present three avenues for future research.